2016
DOI: 10.1098/rsif.2016.0367
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of glycosaminoglycans to the mechanical behaviour of the posterior human sclera

Abstract: We characterized the structural and mechanical changes after experimental digestion of sulfated glycosaminoglycans (s-GAGs) in the human posterior sclera, using ultrasound thickness measurements and an inflation test with three-dimensional digital image correlation (3D-DIC). Each scleral specimen was first incubated in a buffer solution to return to full hydration, inflation tested, treated in a buffer solution with chondroitinase ABC (ChABC), then inflation tested again. After each test series, the thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 66 publications
4
39
2
Order By: Relevance
“…Enzymatic digestion of post mortem human ONH alters its biomechanical properties (Spoerl et al, 2005), and digestion with chondroitinase alters scleral strain in porcine globes in the opposite direction to that seen with GA treatment (Murienne et al, 2013). Investigations of experimental glaucoma both in monkeys (Burgoyne et al, 2005) and mice (Cone et al, 2010) suggest that both baseline scleral structure and its dynamic response to elevated IOP may be important determinants of glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic digestion of post mortem human ONH alters its biomechanical properties (Spoerl et al, 2005), and digestion with chondroitinase alters scleral strain in porcine globes in the opposite direction to that seen with GA treatment (Murienne et al, 2013). Investigations of experimental glaucoma both in monkeys (Burgoyne et al, 2005) and mice (Cone et al, 2010) suggest that both baseline scleral structure and its dynamic response to elevated IOP may be important determinants of glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a relation between sGAG content and mechanical response of the sclera might exist. In support of this hypothesis, recent experiments have shown that sGAGs had a significant effect on inflation mechanical behavior of sclera [24,25]. In particular, it was seen that sGAG removal led to an overall more compliant mechanical behavior of porcine sclera.…”
Section: Discussionmentioning
confidence: 71%
“…The mechanical function of sGAGs in tissues such as tendon [13][14][15][16][17], ligament [18,19], and articular cartilage [20][21][22] has been extensively examined; however, their possible effects on mechanical properties of scleral tissue have been less studied [23][24][25]. Furthermore, pressure-controlled inflation experiments showed that sGAG removal had different effects on human porcine samples, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18,19 As such, depletion or misregulation of GAGs is often associated with natural aging 20 or debilitating diseases. [21][22][23] Notably, it has been proposed that misregulation of GAGs perturbs the mechanobiology of the ECM, leading to a loss of biological function and aberrant cell activity. 7 However, the mechanism and extent to which GAGs alter individual collagen fibrils has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%